The Filistatidae in the Caribbean region, with a description of the new genus Antilloides, revision of the genus Filistatoides F. O. P.-Cambridge and notes on Kukulcania Lehtinen (Arachnida, Araneae) - Brescovit, Antonio D.; Ruiz, Alexander Sánchez; Garcia, Giraldo Alayón (Zootaxa, 2016)
A synopsis of Caribbean filistatid diversity is recorded herein. A new genus, Antilloides, is proposed for five new species exclusively found in the Antilles: A. abeli n. sp., A. cubitas n. sp., and A. mesoliticus n. sp. from Cuba; A. haitises n. sp. from the Dominican Republic; and A. zozo n. sp. from the U. S. Virgin Islands and Puerto Rico. The genus Filistatoides is revised and includes four species: the type species F. insignis F.O.P. Cambridge, which occurs only in Guatemala; the female is described here for the first time; F. polita Franganillo sp. reval., comb. nov., which occurs only in Cuba; F. xichu n. sp. described from Mexico; and F. milloti (Zapfe) which does not appear to belong to the genus based on morphological structures. Additionally, Kukulcania isolinae Alayón is synonymized with Kukulcania hibernalis (Hentz), and new records of its distribution are included for the Greater and Lesser Antilles.